Desakralisasi Makna Keris: Studi Etnografi Pada Ahli Waris Keris - Lestari, Siti Putri (Umbara, 2024)
Kris has been known as a sacred object; and often passed down by the owner to their descendants as inheritance. Through this process the assumption about Kris as the sacred object is maintained. However, nowadays, people no longer consider Kris as a valuable and sacred object as before, and some of them refuse to inherit a Kris from their parents. This research describes the meaning of Kris for people who inherit it from their parents and ancestors; what is their attitude toward Kris and how their attitude may represent the desacralization of Kris. This research was conducted in an ethnographic approach. Data collected through observation, in-depth interviews and literature review. Clifford Geertz’s symbolic interpretation theory was used as the framework of analysis. Findings of this research suggest that the heirs of Kris often interpret it as an ordinary object; and they no longer view the essence and nobility of Kris. This view leads them to develop skepticism towards the mystical phenomenon of Kris. Sometimes, they even refuse to inherit Kris due to social, cultural and religious considerations. In some cases, they consider Kris as a burden to them. These phenomena demonstrated how Kris loses its sacred dimension nowadays.